Field notes contributed by multiple observers, summer 1993 - Jackson, Laura Spesset al; Wilson, Marloweet al; Robinson, Randyet al; Klein, Mikeet al (1993)
Summer report of birds and locations contributed by multiple observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1993. Plustek - flatbed